2016
DOI: 10.1016/j.dadm.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive complaints in older adults at risk for Alzheimer's disease are associated with altered resting‐state networks

Abstract: IntroductionPathophysiological changes that accompany early clinical symptoms in prodromal Alzheimer's disease (AD) may have a disruptive influence on brain networks. We investigated resting-state functional magnetic resonance imaging (rsfMRI), combined with brain connectomics, to assess changes in whole-brain functional connectivity (FC) in relation to neurocognitive variables.MethodsParticipants included 58 older adults who underwent rsfMRI. Individual FC matrices were computed based on a 278-region parcella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 49 publications
6
64
0
Order By: Relevance
“…In addition, AD brains accumulate Aβ, tau, and a number of other proteins, suggesting the failure of shared protein turnover pathways 4,116 . However, pathogenesis of AD is now recognized as beginning well before obvious "pathology" can be detected [117][118][119] . In addition, the potential diseasemodifying activity of rivastigmine may be due not so much to reduction of Aβ but stimulation of neurotrophic sAPPα production and other effects of ADAM proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AD brains accumulate Aβ, tau, and a number of other proteins, suggesting the failure of shared protein turnover pathways 4,116 . However, pathogenesis of AD is now recognized as beginning well before obvious "pathology" can be detected [117][118][119] . In addition, the potential diseasemodifying activity of rivastigmine may be due not so much to reduction of Aβ but stimulation of neurotrophic sAPPα production and other effects of ADAM proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that people can maintain good cognitive abilities and successful day-to-day functioning despite significant neuronal loss and atrophy. This disjunction between structure and function is a feature of healthy ageing, but we have shown that it also characterises presymptomatic FTD, over and [39] and dementia [38]. Here, we show the significance of the maintenance of this functional network organisation, with a progressively stronger correlation with cognitive performance as seemingly healthy adults approach the age of expected onset of FTD.…”
Section: Discussionmentioning
confidence: 50%
“… Zhang, et al 2016 [103] 76 aMCI, 19 ADD, 23 CNC RAVLT, MMSE, ADAS, Logical Memory I and II Functional connectivity between 18ROIs/Aβ PET, APOE ε4 status Medial frontal gyrus and parahippocampus functional connectivity negatively correlated with memory in aMCI and ADD. Contreras, et al 2017 [104] 21 aMCI, 8 ADD, 16 subjective cognitive decline, 13 CNC CVLT-II ICA (resting-state network, visual network, DMN and frontoparietal network) DMN and frontoparietal network connectivity positively correlated with recall. Abbreviations: APOE ε4, apolipoprotein E ε4; CNC, cognitively normal control; aMCI, amnestic mild cognitive impairment; MCI, mild cognitive impairment; naMCI, nonamnestic mild cognitive impairment; Aβ, amyloidβ; ADD, Alzheimer's disease dementia; RAVLT, Rey Auditory Verbal Learning Test; AVLT, Auditory Verbal Learning Test; RCFT, Rey Complex Figure Test; CVLT, California Verbal Learning Test; WMS, Wechsler Memory Scale; ADAS, Alzheimer's Disease Assessment Scales; MMSE, Mini–Mental State Examination; CERAD-WL, Consortium to Establish a Registry for Alzheimer's Disease-Word list; DMN, default mode network; ECN, executive control network; PCG, posterior cingulate gyrus; R, right; PFC, prefrontal cortex; VBM, voxel-based morphometry; L, left; PiB PET, Pittsburgh compound B positron emission tomography; ICA, independent component analysis; HC, hippocampus; DG, dentate gyrus; MTL, medial temporal lobe; HC, hippocampus; GM, gray matter; FDG-PET, fluorodeoxyglucose positron emission tomography; ROI, region of interest.…”
Section: Functional Mrimentioning
confidence: 99%